2017
DOI: 10.5195/jmla.2017.178
|View full text |Cite
|
Sign up to set email alerts
|

The role of librarians in teaching evidence-based medicine to pediatric residents: a survey of pediatric residency program directors

Abstract: Objective:The research sought to identify the general use of medical librarians in pediatric residency training, to define the role of medical librarians in teaching evidence-based medicine (EBM) to pediatric residents, and to describe strategies and curricula for teaching EBM used in pediatric residency training programs.Methods:We sent a 13-question web-based survey through the Association of Pediatric Program Directors to 200 pediatric residency program directors between August and December 2015.Results:A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Overall, our results suggested that the intervention was successful in teaching students about library resources and that prior experience, such as attending other voluntary lecture series, is not a mediator of the observed improvement. Moreover, our results agreed with previous studies showing that collaborating with librarians in EBM education would help medical students get familiar with EBM-relevant resources provided by libraries (24). As the awareness of accessible EBM-relevant resources and services provided by library were boosted (Table 3), our intervention was able to alleviate common challenges that students were confronted with while learning and familiarizing themselves with EBM.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, our results suggested that the intervention was successful in teaching students about library resources and that prior experience, such as attending other voluntary lecture series, is not a mediator of the observed improvement. Moreover, our results agreed with previous studies showing that collaborating with librarians in EBM education would help medical students get familiar with EBM-relevant resources provided by libraries (24). As the awareness of accessible EBM-relevant resources and services provided by library were boosted (Table 3), our intervention was able to alleviate common challenges that students were confronted with while learning and familiarizing themselves with EBM.…”
Section: Discussionsupporting
confidence: 88%
“…The response rate was comparable to those of some other surveys recently distributed by the APPD, 24,25 though lower than some others. 26,27 Because we lack information on nonrespondents, we are unable to assess potential sources of nonresponse bias. For example, the sample may disproportionately represent programs that have multiple APDs, any or all of whom could have responded to the survey.…”
Section: Discussionmentioning
confidence: 99%
“…18 Librarians have been involved in various EBHP-related activities, such as being part of patient care teams for morning report presentations, attending morning rounds, participating in literature reviews relevant to clinical cases (which result in shortened length of stay in hospital for patients), consulting to provide ''just in time'' literature searches for clinical questions, assisting with the integration of research into evidence-based medicine curricular, as well as locating studies relevant to patient care. 19 Despite the importance of librarians in EBHP, little attention has been paid to the perceptions and attitudes of health care professionals toward the involvement of librarians in producing evidencebased research and participation in other EBHP-related activities. 20,21 Many health care professionals lack the literature-searching skills and are therefore reluctant to conduct searches for evidence in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, because they are unaware of librarians' capacity to participate in EBHP, they do not request their assistance, and, therefore, librarians' expertise is underutilized. 23 Even when librarians are willing to participate, they may not be aware of which research activities are taking place unless they are invited to contribute. Furthermore, librarians' roles differ, depending on their job descriptions and capabilities.…”
Section: Introductionmentioning
confidence: 99%